Analysis of peri-implant tissue post-implantation using periapical radiograph: a scoping review - Lazaro Nehemia Benedict Dilens; Azhari Azhari; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This review article is aimed to review various studies evaluating changes in peri-implant height and bone density post-implantation using periapical radiographs. Review: This scoping review was carried out according to Preferred Reporting Items for Systematic Review and Meta-analysis for Scoping Review (PRISMA-Scr) by reviewing literatures related to the evaluation of peri-implant bone post-implantation using periapical radiographs. PRISMA-ScR is a guide for writing a scoping review to increase the relevance and transparency of methodological and research findings. Literature searches were performed on PubMed NCBI, Science Direct, EBSCOHost, and Clinicalkey databases with the keywords “((dental implant) AND (periapical radiograph)) AND (peri-implant) OR (alveolar bone))”. Literature screening was carried out based on the predetermined inclusion and exclusion criteria that have been set in journals published in 2016-2020. A total of 18 eligible studies were included in this study. The data from the included studies was then synthesized, and the literatures were reviewed. Conclusion: Peri-implant bone generally experiences a decrease in height (marginal bone loss) and an increase in density during the process of bone adaptation to functional loading. The design and placement techniques of the implants have an impact on the extent of the change in bone height.